Ganho genético em caracteres agronômicos, fenológicos e bioquímicos de soja no Brasil - Milioli, Anderson Simionato (2021)
Soybean is one of the main crops produced worldwide, and the on-farm yields has increased considerably in the last decades in Brazil. To evaluate the genetic gainfor agronomic, phenological and biochemical traits, soybean cultivars released from 1966 to 2011 were evaluated in the main regions of soybean cultivation in Brazil. The field trials were conducted in 25 environments (site-year) in South region, 14 in Midwest region, and eightin North and Northeast regions in 2016/17, 2017/18 and 2018/19 crops seasons. The best linear unbiased predictors (BLUP) of each trait were obtained using a mixed linear model. The BLUPsand years of cultivar release were used in the regression analysis to obtain genetic gain rates. The linear gain rates for seed yield in South region were 15.31, 13.83 and 14.13 kg ha-1year-1(0.42, 0.36 and 0.39% year-1) for the full, early and medium sets of cultivars, respectively. The quadratic model also showed a trend to increase the gain rates in the last years of the historical serie, although the fit was not significant. In addition, new cultivars presented more plant height, seed oil content, and oil and protein yield, and less seed weight, days to flowering, days to maturity and seed protein content than old ones, although there were significant differences between the macroregions 1 and 2. In the Midwest region, the linear gain rates for seed yield were 17.55, 13.58, 21.84 and 20.83 kg ha-1year-1(0.62, 0.47, 0.77 and 0.69% year-1) for the full, early, medium and late sets of cultivars, respectively. The new cultivars presented more seed oil content, oil and protein yield, and less seed proteinand lower first pod insertion than old ones. There was also a trend to reduce days to maturity and days to flowering over the years. Regarding the North and Northeast regions, were not identified significant gains for the most of the evaluated traits. Theresults shown that breeding programs has been efficient across the years to improve soybean yield and important traits in the main producing regions of Brazil, and that a yield plateau has not been reached yet.